(untitled) (American Journal of Islam and Society, 2005)
The Sixth Annual Conference of the Islamic Social Services Association (ISSA) was held June 17-19, 2005, at Arizona State University (ASU) and the Holiday Inn in Tempe, Arizona. Sponsors included the Department of Social Work, ASU at the West Campus; the School of Social Work, ASU at the Tempe Campus; the National Association of Social Workers–Arizona chapter; the Muslim American Society–Arizona chapter; the Council on American Islamic Relations–Arizona chapter; the Muslim Students Association at ASU Tempe Campus; the Muslim Law Students’Association at ASU; the Islamic Center of the East Valley; and Global Medical Technologies. The conference and pre-conference institute continued ISSA’s mission: promoting awareness of the social welfare, mental health, and family concerns facing Muslims in North America by educating mainstream providers, Muslim practitioners involved in providing human services, imams, and community leaders. The pre-conference institute’s theme was “Muslim Culture and Faith,” the title of ISSA’s anti-bias project training for mainstream providers. The conference’s theme was “Islamic Social Services: Challenges and Opportunities.” Pre-conference institute presenters Aneesah Nadir (Arizona State University and ISSA–USA) and Shahina Siddiqui (ISSA–Canada) provided information about Muslim culture, traditions, beliefs, the history of Islam and Muslims in North America, and social issues facing Muslims, as well as guidelines and considerations for addressing the social issues that Muslims’ experience. Social workers, counselors, teachers, health-care and mental-health providers from mainstream social service organizations, public and private schools attended the pre-conference institute. Social work educators, doctoral candidates, and Muslim community social service providers were among the presenters for the overall ISSA conference. Abdul Malik Mujahid (Soundvision), Omar Shahin (National Association of Imams Federation [NAIF]), Mohamed Magid (All Dulles Area Muslim Society [ADAMS]) and Bonita McGee (ISSA–USA) facilitated discussions with imams and community leaders. This session explored ways imams can address social issues and strategies Muslim social service providers can employ to help them meet the community’s social needs. While the imams identified a complex situation with a variety of problems and solutions, it became clear that they do not have the knowledge and skills to address the community’s many social and family issues. Opportunities for consultation and education with imams and mosque leaders are necessary, therefore, organizations like NAIF are working with ISSA to provide this to their members. Imams also need to be recognized as professionals with clear job descriptions and regular (including counseling) hours. One imam is not enough; perhaps youth imams and assistant imams are needed ...